Different clinical characteristics and outcomes of adult hospitalized SARS-CoV-2 pneumonia patients complicated by cardiovascular events during the first, delta and omicron waves of COVID-19 - Roser, Lynn P.; Samanapally, Harideep; Ali, T’shura; Xu, Qian; Han, Yuchen; Salunkhe, Vidyulata; Deepti, Fnu; McGuffin, Trevor; Huang, Emma C.; Furmanek, Stephen; Glynn, Alex; Ramirez, Julio; et al. (Frontiers in Epidemiology, 2024)
Background: The effects of SARS-CoV-2 have varied between significant waves of hospitalization. Research Question: Are cardiovascular complications different among the first, delta and omicron waves of hospitalized COVID-19 pneumonia patients? Study Design and Methods: This was a multi-centre retrospective study of patients hospitalized with SARS-CoV-2 pneumonia: 632 were hospitalized during the first wave (March–July 2020), 1013 during the delta wave (September 2020–March 2021), and 323 during the omicron wave (January 2022-July 2022). Patients were stratified by wave and occurrence of cardiovascular events. Results: Among all hospitalized patients with cardiovascular events, patients in the omicron wave were younger (62.4 ±14 years) than patients in the first wave (67.4 ±7.8 years) and the delta wave (66.9 ±12.6 years) and had a higher proportion of non-Hispanic White people than in the first wave (78.6% vs 61.7%). For COVID-19 patients who suffered from cardiovascular events, the omicron wave patients had significantly higher neutrophil/lymphocyte ratio, white blood cell and platelet counts when compared to the first wave. Omicron wave patients had significantly lower albumin and B-type natriuretic peptide levels (only 5.8% of the first wave and 14.6% of the delta wave) when compared to either the first wave or delta wave patients. In COVID-19 patients who suffered cardiovascular events during hospitalization, mortality rate in the omicron wave (26.8%) was significantly lower than the first wave (48.3%), time to mortality for non-survivors of COVID-19 patients who suffered cardiovascular events was significantly longer in the omicron wave (median 16 days) than in the first wave (median 10 days). Conclusions: Younger and white patients were affected with cardiovascular complications more often by the omicron variant. Despite higher neutrophil/lymphocyte ratio and WBC counts, the omicron patients with cardiovascular events showed lower heart injuries, lower mortality and longer time to mortality for non-survivors when compared to the first and delta waves.